IMPROVING PEDAGOGICAL AND PSYCHOLOGICAL PREPARATION OF STUDENTS FOR THE FORMATION OF SOCIAL ADJUSTMENT IN CHILDREN - Inamova Maxliyo (International Scientific and Current Research Conferences, 2023)
Proverbs can be called an encyclopedia of life, a folk encyclopedia, a kind of artistic and historical chronicle. They sharpen people's minds, make their speech clear and expressive, teach them to choose the right path in life, to solve life's riddles and problems correctly. Proverbs are also very ancient as the smallest examples of oral creativity, summarizing the worldview, cultural, everyday and mental treasure of the people who created them. The article talks about the role of folk proverbs in the development of the speech culture of children in preschool educational institutions.